Compositional and microstructural outlook of grave goods from Anta do Malhão and Soalheironas (Portugal): the diachronic use of arsenical copper in southwestern Iberian Peninsula - Valério, Pedro (2021)
Although in recent years the prehistoric metallurgy of southwestern Iberian Peninsula has become increasingly well understood, the southernmost region still requires additional research. This work presents the technological study of artefacts from burial contexts located in this area, namely the necropolises of Anta do Malhão and Soalheironas (Algarve region). Typologies of metalwork and pottery ascribe the single inhumation at Anta do Malhão to a late phase of the “Ferradeira Horizon” (last quarter of the 3rd millennium BC), while assigning the necropolis of cists at Soalheironas to an earlier phase of the Middle Bronze Age (1st half of the 2nd millennium BC). The elemental and microstructural composition of artefacts was established by micro-energy dispersive Xray fluorescence spectrometry, optical microscopy and scanning electron microscopy with X-ray microanalysis. Results show artefacts made of arsenical copper alloys (2.01–3.40% As) with very low iron content (< 0.05% Fe). The microstructures display deformed equiaxed grains with annealing twins and slip bands, evidencing cycles of hammering and annealing, followed by a finishing hammering operation. The integration of results in the prehistoric metallurgy of southwestern Iberian Peninsula suggests a shared technological tradition, while a more comprehensive discussion discloses important developments involving the increased production of strainhardened tools and weapons, together with a rising substitution of the copper metal by arsenical copper alloys from the 3rd to the 2nd millennium BC.